Exploring the effectiveness of a novel memory training program for students with learning disabilities in the United Arab Emirates: investigating the role of gender differences - Alghazo, Emad; Abo Hamza, Eid; Bedewy, Dalia (Frontiers in Education, 2024)
Introduction The present research aims to investigate the efficacy of a newly developed memory training strategy on improving the memory capabilities of students with learning impairments. Methods Involving thirty male and female students with learning challenges, the study divided participants into experimental and control groups, with the former undergoing a novel memory training program. Memory was evaluated before and after a 3-month training period using a recall assessment technique developed from prior studies. Results Findings indicated statistically significant differences in memory scores between the experimental and control groups on the novel memory scale (total score) and its aspects (Auditory, Visual, and Visual kinesthetic memory), with improvements noted only in the experimental group. Gender did not significantly impact the scores, and there was no significant interaction between gender and group on training outcomes, suggesting the training's universal applicability. Discussion The study demonstrates that a novel memory training course can significantly enhance memory functions in students with learning impairments, irrespective of gender. These results offer promising directions for integrating cognitive training into educational strategies to support students facing learning challenges.